A CASE STUDY OF THE USE OF SLANG IN THE INTERACTION AND FRIENDSHIP CIRCLE OF CLASS F ENGLISH LITERATURE UIN BANDUNG (Argopuro: Jurnal Ilmu Bahasa, 2025)
This research is a case study that discusses the use of slang in the author's interaction with the circle of friends in Class F of the English Literature Study Program at UIN Bandung. The background of this research is the phenomenon of the increasing use of slang among teenagers, including university students, as part of the expression of identity, familiarity, and group social dynamics. This study aims to describe the forms of slang and slang used, understand its function in social interaction, and examine its influence on the use of good and correct Indonesian. The method used is descriptive qualitative through observation and documentation of conversations, as well as the study of relevant literature. The results show that slang has become part of daily communication that is considered “familiar” and contextual in the student environment. However, the intensity of the use of this language also has an impact on reducing the existence of the use of formal Indonesian, causing misunderstandings of meaning, and obscuring standard language structures. This research emphasizes the importance of language awareness among adolescents and university students, in order to adjust the use of language to the context of communication, and still maintain the function of Indonesian as a good and correct national language.  This study explores the use of language particularly the integration of Bahasa Indonesia and slang within the friendship circle of Class F students majoring in English Literature at UIN Sunan Gunung Djati Bandung. The research aims to examine how language is used in daily interactions among peers, especially considering the increasing influence of technology on communication patterns. Through a quantitative descriptive method using questionnaires, findings reveal that the use of Bahasa Indonesia remains dominant among the students, with a consistently high score (5) across nearly all questionnaire items. In addition, the presence and frequent use of slang among students, especially outside formal learning hours, reflect the dynamic nature of language shaped by Generation Z's preferences and digital culture. These results highlight how both native language and informal linguistic trends coexist and evolve within academic and social settings. The study provides insights for future language planning and communication strategies that resonate with the linguistic identity of today’s youth.  Penelitian ini merupakan studi kasus yang membahas penggunaan bahasa gaul dalam interaksi penulis dengan lingkaran pertemanan di Kelas F Program Studi Sastra Inggris UIN Bandung. Latar belakang dari penelitian ini adalah fenomena meningkatnya penggunaan bahasa gaul di kalangan remaja, termasuk mahasiswa, sebagai bagian dari ekspresi identitas, keakraban, dan dinamika sosial kelompok. Penelitian ini bertujuan untuk mendeskripsikan bentuk dan jenis bahasa gaul yang digunakan, memahami fungsinya dalam interaksi sosial, serta mengkaji pengaruhnya terhadap penggunaan bahasa Indonesia yang baik dan benar. Metode yang digunakan adalah deskriptif kualitatif melalui observasi dan dokumentasi percakapan, serta kajian pustaka yang relevan. Hasil penelitian menunjukkan bahwa bahasa gaul telah menjadi bagian dari komunikasi sehari-hari yang dianggap “akrab” dan kontekstual di lingkungan mahasiswa. Namun, intensitas penggunaan bahasa ini juga berdampak pada berkurangnya penggunaan bahasa Indonesia formal, menimbulkan kesalahpahaman makna, dan mengaburkan struktur bahasa baku. Penelitian ini menekankan pentingnya kesadaran berbahasa di kalangan remaja dan mahasiswa, agar dapat menyesuaikan penggunaan bahasa dengan konteks komunikasi, namun tetap menjaga fungsi bahasa Indonesia sebagai bahasa nasional yang baik dan benar. Penelitian ini juga mengeksplorasi penggunaan bahasa, khususnya integrasi antara Bahasa Indonesia dan bahasa gaul dalam lingkar pertemanan mahasiswa Kelas F jurusan Sastra Inggris di UIN Sunan Gunung Djati Bandung. Penelitian ini bertujuan untuk mengkaji bagaimana bahasa digunakan dalam interaksi sehari-hari antar teman, terutama dengan mempertimbangkan pengaruh teknologi yang semakin besar terhadap pola komunikasi. Melalui metode deskriptif kuantitatif dengan menggunakan kuesioner, temuan menunjukkan bahwa penggunaan Bahasa Indonesia tetap dominan di kalangan mahasiswa, dengan skor tinggi yang konsisten (5) pada hampir semua butir kuesioner. Selain itu, keberadaan dan frekuensi penggunaan bahasa gaul, terutama di luar jam belajar formal, mencerminkan sifat dinamis bahasa yang dibentuk oleh preferensi Generasi Z dan budaya digital. Hasil ini menyoroti bagaimana bahasa asli dan tren linguistik informal dapat hidup berdampingan dan berkembang dalam konteks akademik dan sosial. Studi ini memberikan wawasan bagi perencanaan bahasa dan strategi komunikasi di masa depan yang selaras dengan identitas linguistik generasi muda saat ini.